1984
DOI: 10.1136/thx.39.5.376
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary infection with mycobacterium xenopi: review of treatment and response.

Abstract: ABsTRAcr Forty seven patients (82 % male) with pulmonary infection caused by Mycobacterium xenopi have been reviewed. Pre-existing lung disease was present in 35 (75 %). In 21 patients the disease was characterised by a subacute illness developing over a period of two to four months, while in another 20 patients there was a longer history of chronic respiratory problems often associated with slowly progressive changes evident from chest radiographs. Response to treatment was poor and unpredictable, and was not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
4

Year Published

1989
1989
2004
2004

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(42 citation statements)
references
References 10 publications
1
37
0
4
Order By: Relevance
“…In 15 of these patients, pulmonary disease due to this organism was suspected. Banks et al [77] reviewed treatment and response in patients with pulmonary mycobacteriosis due to M. xenopi in 1984. Of the 47 patients, 39 (83%) were men, and the mean age of the group was 61.5 years (range, 36-84 years).…”
Section: Site Of Mycobacteriosismentioning
confidence: 99%
“…In 15 of these patients, pulmonary disease due to this organism was suspected. Banks et al [77] reviewed treatment and response in patients with pulmonary mycobacteriosis due to M. xenopi in 1984. Of the 47 patients, 39 (83%) were men, and the mean age of the group was 61.5 years (range, 36-84 years).…”
Section: Site Of Mycobacteriosismentioning
confidence: 99%
“…He showed satisfactory clinical and bacteriological responses after the regimen was changed, based on the results of susceptibility testing. Banks et al reported that there was a poor correlation between in vitro susceptibility results and clinical response (7). In the present two cases, pulmonary infection due to M. xenopi was successfully treated not with first-line drugs but with drugs to which the organisms had shownin vitro susceptibility.…”
Section: Discussionmentioning
confidence: 60%
“…Since then, this organism has been isolated both as an environmental contaminant, particularly from hot water systems, and as a presumedetiologic agent of human disease (2)(3)(4). The prevalence of M. xenopi varies geographically, being one of the most commonlyisolated nontuberculous mycobacteria in France (5), England (6,7) and Canada (8), and less commonly identified in the USA (9) and Sweden ( 10). In Japan, few cases have appeared in the literature since the first case of-lung infection due to M. xenopi was reported in 1984 (ll, 12).…”
Section: Introductionmentioning
confidence: 99%
“…Retrospective studies have shown that patients treated for 18-24 mo with regimens that included rifampicin and ethambutol did better than those treated with other regimens or who had shorter durations of treatment (32). The addition of second-or thirdline drugs increased the rate at which adverse events were reported without improving the outcome.…”
Section: Pulmonary Diseasementioning
confidence: 99%
“…Therefore, it will be present in multiple specimens, thus passing the test for "significance," although in many such cases it is not responsible for clinical symptoms. In addition, infection with M. xenopi is normally indolent, with disease developing over a number of years (32). Thus, an isolate in an apparently asymptomatic patient cannot be lightly dismissed, especially in HIV-infected individuals.…”
Section: Pulmonary Diseasementioning
confidence: 99%